David B. Quinn papers - Quinn, David B.
Correspondence detailing all aspects of Quinn's teaching, research, and publishing careers; correspondence, minutes, reports, appointment calendars, applications, autobiographical sketches, clippings, photographs, and other papers pertaining to the Hakluyt Society of which Quinn was president, to historical and editorial committees on which he served, and to his involvement with the British Labour and Communist parties; research files consisting of notes and transcriptions of charters, chronicles, colonization tracts, correspondence, court records, drawings, financial accounts, land records, maps, state papers, statutes, travel literature, and other documents relating to British exploration and settlement of North America from the late fifteenth to early seventeenth centuries and to the English colonization of Ireland in the sixteenth century; and lectures, writings, and papers presented by Quinn on these and other topics.
Includes research material on the activities of Thomas Cavendish, Sir Francis Drake, Sir Humphrey Gilbert, Richard Hakluyt, Thomas Hariot, Stephanus Parmenius, Sir Walter Raleigh, and John White, governor of the Roanoke colony. Also includes material on Quinn's expeditions relating to English colonial sites at Roanoke Island, N.C., and Saint Marys City, Md., his Fulbright lectures in the United States, and other history projects. Correspondents include Kenneth R. Andrews, J. C. Beckett, Nicholas P. Canny, R. Dudley Edwards, Steven G. Ellis, Christopher Hill, T. W. Moody, Samuel Eliot Morison, and J. E. Todd.
Microfilm edition only for portions of Quinn's research material
Microfilm reproduced from from originials in repositories in England, Ireland, Netherlands, Spain, United States, and Wales.
British historian. Full name: David Beers Quinn. Born 1909.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Andrews, Kenneth R. -- Correspondence; Beckett, J. C. -- 1912- -- Correspondence; Canny, Nicholas P. -- Correspondence; Cavendish, Thomas, -- 1560-1592.; Drake, Francis, -- 1540?-1596.; Edwards, R. Dudley -- 1909- -- Correspondence; Ellis, Steven G., -- 1950- -- Correspondence; Gilbert, Humphrey, -- Sir, -- 1539?-1583.; Hakluyt, Richard, -- 1552?-1616.; Harriot, Thomas, -- 1560-1621.; Hill, Christopher, -- 1912-2003 -- Correspondence; Moody, T. W. -- 1907- -- Correspondence; Morison, Samuel Eliot, -- 1887-1976 -- Correspondence; Parmenius, Stephanus, -- -1583.; Raleigh, Walter, -- Sir, -- 1552?-1618.; Todd, J. E. -- Correspondence; White, John, -- active 1585-1593.; Communist Party of Great Britain; Hakluyt Society; Labour Party (Great Britain); Historiography -- Great Britain; History -- Research -- Great Britain; History -- Study and teaching -- Great Britain; History -- Societies, etc; History publishing -- Great Britain; Lectures and lecturing; Political parties -- Great Britain; America -- Discovery and exploration -- British; Great Britain -- Colonies -- America; Great Britain -- History -- Sources; Great Britain -- History -- Tudors, 1485-1603.; Great Britain -- Politics and government -- 1936-; Ireland -- History -- 16th century; Maryland -- History -- Colonial period, ca. 1600-1775.; North Carolina -- History -- Colonial period, ca. 1600-1775.; Roanoke Colony; Roanoke Island (N.C.) -- History; Saint Marys City (Md.) -- History; United States -- History -- Colonial period, ca. 1600-1775.; Historians